Structure preservation in content‐aware image retargeting using multi‐operator. Issue 13 (1st November 2020) - Garg, Ankit; Negi, Ashish
Abstract : The evolution of image retargeting technique demands the exploitation of multi‐operators since they are capable of preserving the structure and salient objects of the image. However, these multi‐operators are mostly based on seam carving with scaling or cropping operators which lead to significant distortions in the retargeted image. This study proposes a new multi‐operator scheme which has improved seam carving, through the proposed seam diversion based image retargeting algorithm, integrated with the cropping and warping operator. A total of six different multi‐operator schemes have been proposed out of which the MO6 technique gave remarkable results in terms of image quality, least distortion, and lowest run‐time. To simplify image retargeting operations, an optimised image distance function was used. The optimised image distance function was formulated which combines bidirectional image Euclidean distance, dominant colour descriptor, and an energy‐based coefficient to bypass seams from the point where seams start clashing and hence the defined threshold violates. By integrating cropping and warping into the proposed algorithm, it preserves the salient features of the retargeted images. Typical results have been presented which demonstrates the effectiveness of the proposed methods. User‐based subjective analysis has also been carried out which shows that image retargeted using the MO6 technique has high user preference.